Gamification of Learning: Can Games Motivate Me to Learn History? - Andry Chowanda; Alan Darmasaputra Chowanda (ComTech: Computer, Mathematics and Engineering Applications, 2016)
This article presented empirical finding of the effect of gamification for learning. Evidence in the findings of the empirical study that explores two education games that were developed earlier with a total of 64 participants was presented. The first game was a computer game with historical themes of Ken Arok and Ken Dedes of Singhasari Kingdom. The second game was an Android-based mobile game with Historicity of the Bible themes of Moses. Prior research showed that more than 50 percent of junior and senior high school students in Jakarta demonstrated their apathy to several subjects in their school. They also disclosed that they were having difficulty in following their class in particular with a difficult subject such as History subject. With the popularity of games, the gamification of learning was investigatd to enhance the interest of the students to master a particular subject. The results show that there is a statistical significance increase of the students score and interest in history subject in a group that was using the games to help them in the subject compared to a group that reading books about the particular subject alone 0.001. Furthermore, the participants also reported that playing games was helping them to remember difficult names and event timeline in the historical events